Between Numbers and Logic: How Are Mathematics and Science Learning Outcomes Related? - Ibnu Imam Al Ayyubi; Nurhikmah Nurhikmah; Eko Prayetno; Muhamad Maldini Mahrus; Haifa' Ghitha Rizkiani (JENIUS (Journal of Education Policy and Elementary Education Issues), 2025)
This study aims to analyze the relationship between students' mathematics and science learning outcomes using a mixed methods approach with an explanatory sequential design. The quantitative method examines the correlation between the two variables through the Spearman test, while the qualitative method explores students' experiences in learning mathematics and science through interviews and observations. The study was conducted at SD Inpres Mannurukki with a sample of 25 fifth-grade students selected using purposive sampling. Statistical analysis results indicate no significant relationship between mathematics and science learning outcomes, with a correlation coefficient of -0.067 and a significance value of 0.750 (> 0.05). Interviews with students revealed that they found science concepts easier to understand due to hands-on experiments, whereas mathematics was perceived as more abstract and challenging. These findings suggest that although mathematics and science are logically related, other factors, such as teaching methods and experimental experiences, play a more dominant role in shaping science comprehension. Therefore, it is recommended to implement integrated learning strategies, such as the STEM approach or project-based learning, to enhance the connection between mathematical and scientific concepts in education.